Band gap engineering, electronic state and local atomic structure of Ni doped CeO2 nanoparticles - Kumari, Kavita; Aljawfi, Rezq Naji; Vij, Ankush; Chae, K. H.; Hashim, Mohd.; Alvi, P. A.; Kumar, Shalendra (SPRINGER, 2019)
In cerium dioxide (CeO2) as semiconductor compound, the tuning of band gap energy is a pivotal feature for visible light applications. In this report, nanoparticles (NPs) of Ce1-xNixO2 (0.0x0.10) were synthesized through co-precipitation route. The structural, electronic state and optical band gap were investigated by means of X-ray diffraction (XRD), transmission electron microscopy (TEM), near edge X-ray absorption fine structure (NEXAFS) spectroscopy, Raman scattering and UV-Vis spectroscopy. XRD results revealed the single-phase nanocrystalline behavior of CeO2 with cubic fluorite structure. The electronic configuration of the samples, probed via NEXAFS spectra at Ce M-5,M- 4 edges, demonstrated that the cerium exists in Ce4+ and Ce3+ mixed valence states. The formation of Ce3+ ions in the vicinity of oxygen vacancies (Ov) were assessed also via Raman scattering and XANES spectra at Ce L-3 edge. The estimated concentrations of Ce3+ were increased from 6 to 13% as the Ni content increase from 0 to 10% respectively. Here, the inclusion of Ni2+ ions into CeO2 network induced additional Ov and simultaneously reduced the optical band gap from 3.9eV for pure CeO2 to 2.6eV for 10% Ni doped CeO2 NPs. Therefore, the oxygen loss population seem to be responsible for the band gap reduction. The role of Ov for creating profound donor band near the conduction band and narrowing the band gap energy were discussed.
Keywords: VACANCIES